The ascent of chiefs : Cahokia and Mississippian politics in Native North America - Pauketat, Timothy R. (University of Alabama Press, 1994)
This ambitious book provides a theoretical explanation of how prehistoric Cahokia became a stratified society, and ultimately the pinnacle of Native American cultural achievement north of Mexico. Considering Cahokia in terms of class struggle, Pauketat claims that the political consolidation in this region of the Mississippi Valley happened quite suddenly, around A.D. 1000, after which the lords of Cahokia innovated strategies to preserve their power and ultimately emerged as divine chiefs. The new ideas and new data in this volume will invigorate the debate surrounding one of the mo.